Clima organizacional y desempeño laboral en la empresa de servicios Conser Iquitos 2024 - Aramburu Gutierrez, Carlos Javier (2025)
The study opted for a quantitative analysis approach, obtaining results that showed high reliability in the studied variables, with a Cronbach's Alpha value of 0.970 and 0.819. Furthermore, the Pearson correlation analysis was 0.721, indicating moderate and notable correlation, supported by a significance of 0.000, which validates the proposed relationship hypothesis. Therefore, it was concluded that there is a link between the examined variables.